Comparing the impact of beta-blockers and prostaglandin analogues on ocular surface change in glaucoma patients - M. M. Pupysheva; O. G. Gusarevich; A. A. Gusarevich; T. L. Poloz (Сибирский научный медицинский журнал, 2020)
The connection between glaucoma and ocular surface disease (OSD) is determined more distinct due to increasing research of these chronic and progressive diseases. The purpose of research – an assessment of an impact of beta-blockers and prostaglandin analogues on ocular surface in glaucoma patients. Data and methods. 25 patients (25 eyes) with primary open-angle glaucoma (POAG) were examined: group I – 10 patients (10 eyes) receiving antihypertensive therapy with beta-blocker timolol maleate (monotherapy); group II – 15 patients (15 eyes) receiving prostaglandin analogues (monotherapy); control group – 15 patients (15 eyes) without POAG not receiving eye drops). Results. Total tear production (Schirmer test), the stability of the tear film (Norn test), the degree of conjunctiva and cornea staining with the Bengal pink, ocular surface disease index were similar in patients of groups I and II, while differed from the control group. Measurement of the height of the tear meniscus using optical coherence tomography showed that in patients of group I it was higher than in patients of group II, but in both cases less than in individuals of the control group. Cytological results shows us atrophy, dyskeratosis in group I; proliferation in group II and no changes in normal conjunctival epithelium in group III. Conclusion. Atrophy and dyskeratosis are shown in conjunctival epithelium by using cytological method. These changes lead to abnormality of functioning of conjunctival epithelium. Proliferation may cause an increased blood supply and therefore a hyperemia of conjunctiva. Considering the changes of conjunctival epithelium PA therapy is preferable.